Pregnancy health problems and low birth weight associated with maternal insecure attachment style - SABUNCUOĞLU, OSMAN TALAT (SAGE PUBLICATIONS LTD, 2016)
We aimed to determine the association between attachment style and health problems during pregnancy, as well as perinatal health variables. In 122 mothers who were 2-18 months postpartum, hot flushes, vaginal discharge, back pain, breast tenderness, hair changes, and psychological problems were shown to be associated with insecure attachment as measured by the Adult Attachment Style Questionnaires. Babies born to mothers with insecure attachment were more likely to have a low birth weight. It is vital to increase awareness of insecure attachment style as a risk factor among perinatal health care providers to optimize services.
Keywords: attachment style; birth weight; common symptoms; newborn; pregnancy; POSTNATAL DEPRESSION SCALE; BODY DISSATISFACTION; POSTPARTUM; STRESS; WOMEN; PREVALENCE; VALIDATION; SYMPTOMS; OUTCOMES; TURKEY